Production of capsaicinoids in Saccharomyces cerevisiae - Miefalk, Jacob ; 0009-0007-4652-2110; Carlquist, Magnus ; 0000-0001-8881-8197 (Metabolic Engineering 16, Copenhagen, Denmark, 2025-06-15 - 2025-06-19, 2025)
Capsaicinoids, the alkaloid molecules responsible for the pungency of chili peppers, have notable pharmacological effects. They are potent agonists of TRPV1 (vanilloid receptor 1), which is a key drug target for pain disorder treatments. Capsaicinoids can be extracted from chili peppers, but there are several drawbacks to this, among them the quantity variations and cost. This project investigates the potential of using baker’s yeast, Saccharomyces cerevisiae, to produce novel and structurally diverse capsaicinoids with enhanced bioactivity. Capsaicinoids are synthesized from vanillyl amine and a medium-chain acyl-CoA. These acyl-CoA substrates have different chain lengths, saturation and branching which leads to different capsaicinoids (Muratovska et al 2023). A major challenge to achieve efficient production of capsaicinoids in yeast is the cytotoxic effects of capsaicinoids and their precursors (Muratovska et al 2023). In this project, we are investigating metabolic engineering of the yeast peroxisomal beta-oxidation pathway to generate medium chain acyl-CoAs for capsaicinoid compartmentalisation in the peroxisome to mitigate capsaicinoid toxicity. Data on the development of a beta-oxidation engineering pipeline to achieve capsaicinoid biosynthesis in yeast will be presented. References Muratovska, N. et al. (2022) ‘Towards engineered yeast as production platform for capsaicinoids’, Biotechnology Advances, 59, p. 107989. doi:10.1016/j.biotechadv.2022.107989. Muratovska, N. et al. (2022) ‘Towards engineered yeast as production platform for capsaicinoids’, Biotechnology Advances, 59, p. 107989. doi:10.1016/j.biotechadv.2022.107989.